2015
DOI: 10.1002/jtr.2036
|View full text |Cite
|
Sign up to set email alerts
|

Market Profiling and Positioning of Park Brands in Kenya (Case of Premium and Under‐Utilized Parks)

Abstract: The study sought to investigate the market profiling and positioning of park branding in Kenya. Tourism arrivals in Kenya are currently spatially concentrated in only six parks, which receive 81% of the total number of visitors to the country's 26 wildlife sanctuaries. A descriptive survey design was adopted in the study. Two‐stage cluster sampling technique was adopted. The focus of the study was on four protected areas within the Central Tourism region, Kenya. Cluster analysis indicated that the park brands … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…During the same time, SC was free of lions and had been for several decades (Hugh George Cholmondeley, owner of Soysambu Ranch, personal communication ). Additionally, the levels of human‐related disturbance also varied between sites; LNNP is classified as a “Premium Park” (Maingi, Ondigi, & Wadawi, ) and is the second largest revenue‐producing National Park in Kenya. In 2012, it received 253,500 visitors (Muthoka, Oloko, & Obonyo, ).…”
Section: Methodsmentioning
confidence: 99%
“…During the same time, SC was free of lions and had been for several decades (Hugh George Cholmondeley, owner of Soysambu Ranch, personal communication ). Additionally, the levels of human‐related disturbance also varied between sites; LNNP is classified as a “Premium Park” (Maingi, Ondigi, & Wadawi, ) and is the second largest revenue‐producing National Park in Kenya. In 2012, it received 253,500 visitors (Muthoka, Oloko, & Obonyo, ).…”
Section: Methodsmentioning
confidence: 99%
“…However, a Mainland Chinese study found that travel constraints did not emerge as a significant effect on visiting intention (Zou and Petrick, 2017). To our knowledge, only a few studies reported the role of travel constraints and destination image in visiting propensity to Sub-Saharan Africa (Khan et al, 2020;Avraham and Ketter, 2017;Maingi et al, 2015;Muhohominni and Lubbe, 2017). There is no previous study focusing on the Hong Kong tourism market in particular when examining the relationship between travel intentions to Kenya, destination image, and travel constraints.…”
Section: Travel Constraintsmentioning
confidence: 78%
“…The essence of destination branding also lies in forming overall moving service experiences for customers and influencing them in such a way that they revisit the destination over and over again (White, 2013). Developing destinations also helps in generating stronger and unique competitive advantage and destination repositioning (Hemmonsbey & Knott, 2016;Same & Vasquez, 2014).…”
Section: Introductionmentioning
confidence: 99%